Bacteriological Profile of Pancreatic Juice in Patients with Chronic Pancreatitis - Parida, Salil Kumar; Pottakkat, Biju; Raja, Kalayarasan; Vijayahari, Ranjit; Lakshmi, Chandrasekharan Padma (JOP. Journal of the Pancreas, 2014)
Context Information regarding the association of bacteria in the pancreatic fluid in patients with chronic pancreatitis is limited. Objective This study was designed to analyze the prevalence of bacteria in pancreatic juice in patients with chronic pancreatitis and the association of positive pancreatic fluid culture with pre-operative and post-operative parameters. Methods All patients with chronic pancreatitis who underwent operation from November 2011 to October 2013 were prospectively included in the study. Intra-operatively pancreatic duct fluid was collected and sent for culture sensitivity in all patients. The bacteriology of the fluid was analyzed and was correlated with preoperative, intraoperative and postoperative parameters. Results A total of 26 patients were analyzed. Two patients underwent endoscopic retrograde cholangio-pancreatography (ERCP) preoperatively. Bacteria was present in pancreatic duct fluid in 11 (42%) patients. Both patients who underwent ERCP had positive cultures. Most common organism observed was Escherichia coli (6/11, 55%) followed by Klebsiella pneumonia (3/11, 27%). Five patients with positive culture developed wound infection. Bacteria isolated from the wound were similar to pancreatic fluid. Conclusion Bacteria is commonly present in the pancreatic juice in patients with chronic pancreatitis and its presence may have an effect on the post-operative infections following operations. Based on the pancreatic fluid culture results appropriate antibiotic can be given to the patients who will develop septic complications following surgery. Role of bacteria in the pathogenesis of the chronic calcific pancreatitis needs to be investigated in future studies. Image: Bacteria in pancreatic fluid in patients with chronic pancreatitis.